ROLE OF HIGH-FIELD MAGNETIC RESONANCE IMAGING IN DIAGNOSIS OF BLADDER CANCER (LITERATURE REVIEW) - Е. G. Grigoryev; I. G. Frolova; Е. А. Usynin; S. А. Velichko; V. V. Okunev; А. V. Goldberg (Сибирский онкологический журнал)
The role of high-field magnetic resonance imaging in diagnosis and assessment of invasion and local spread of bladder cancer has been presented.